Misreading Tertullian and Other Remarks on 1 Cor 14:34-35: A Response to Joseph Wilson - Lavrinovica, Alesja (TC, 2024)
This note is a short response to the article published by Joseph Wilson entitled “Recasting Paul as a Chauvinist within the Western Text-Type Manuscript Tradition: Implications for the Authorship Debate on 1 Corinthians 14.34–35.” In his article, Wilson aims to strengthen the arguments used by advocates of the so-called Corinthian slogan theory or the quotation/refutation (abbreviated Q/R) hypothesis, which considers 1 Cor 14:34–35 to be a Corinthian slogan that Paul refutes by two strong questions contained in verse 36. In addition to restating a special reading of verse 36 due to the two disjunctive particles ἤ that introduce the questions of verse 36, Wilson intensifies the Q/R hypothesis by reading 1 Cor 14:34–35 in light of Tertullian’s Against Marcion. Wilson suspects that it was Tertullian who introduced a chauvinistic reading of 1 Cor 14:34–36. Here I argue that Wilson misreads Tertullian, and I demonstrate that the interpretation of the syntactical function of the disjunctive particles as argued by the defenders of the Q/R hypothesis is untenable.